Three Šulgi Hymns. Sumerian Royal Hymns Glorifying King Šulgi of Ur - Klein, Jacob (1981)
Bar-Ilan Studies in Near Eastern Languages and Culture. Publications of the Bar-Ilan University, Institute of Assyriology; $28.00